Effect of The Addition of Whey Protein-Basil Seed Gum on The Quality, Properties, and Antioxidant Activities of Low-Fat Mayonnaise: Manufacture of low-fat mayonnaise using whey protein-basil seed gum - Kim, Young-soon; Kim, Si Yeon; bin O, Hyeon; Lee, Phyrim (Progress in Nutrition, 2021)
In this study, our aim was to develop 50% fat reduced mayonnaise using whey protein isolate (5%) -basil seed gum (BSG) complex, and analyze its physicochemical, storage stability and sensory evaluation. Five different samples were prepared with different concentration of BSG complexes (0 %, 0.2%, 0.4%, 0.6% and 0.8%). The pH and viscosity increased significantly with increasing concentration of basil seed gum complexes(p